The impact of tumor associated macrophages on tumor biology under the lens of mathematical modelling: A review - Shojaee, Pejman; Mornata, Federica; Deutsch, Andreas; Locati, Massimo; Hatzikirou, Haralampos (Frontiers in Immunology, 2022)
In this article, we review the role of mathematical modelling to elucidate the impact of tumour-associated macrophages (TAMs) in tumour progression and therapy design. We first outline the biology of TAMs, current application in tumour therapies, and their experimental methods that provide insights into tumour cell-macrophage interactions. We then focus on the mechanistic mathematical models describing the role of macrophages as drug carriers, the impact of macrophage polarised activation on tumour growth, and the role of tumour microenvironment (TME) parameters on the tumour-macrophage interactions. This review aims to identify the synergies between biological and mathematical approaches that allow us to translate knowledge on fundamental TAMs biology in addressing current clinical challenges.